Low-altitude unmanned aerial vehicles for the rapid and high-resolution determination of contamination - Martin, Peter (Cranfield University, 2016)
Poster presentation at the 2016 Defence and Security Doctoral Symposium. Following the events of March 2011 at the Fukushima Daiichi Nuclear Power Plant (FDNPP), a considerable quantity of radiation was released into the local Japanese as well as the global environment. Much work and expense is currently being devoted to the remediation of a large area of eastern Japan contaminated primarily by radiocaesium. Due to the complex nature of the environment affected by the release, it is important to understand contaminant evolution/migration at the greatest possible resolution –  previous airborne survey methods have lacked this high spatial resolution. Initially after the incident, a primary survey of contamination was performed by the US Department of Energy (US DoE) in collaboration with the Japanese MEXT producing a resolution of hundreds of meters per pixel. This survey illustrated the large-scale trend of the contamination influencing the initial evacuation of those in immediate risk. Increased resolution was provided by unmanned helicopters over the years since the event, reducing the pixel size down to a 24 m radius. The work presented here is the combined use of a low altitude multirotor unmanned aerial vehicle (UAV) coupled with a lightweight radiation detection and mapping system. Using this platform, it was possible to measure the current distribution of radionuclide contamination in Japan at a resolution greater than that previously achievable, with sub-meter resolution. Unlike ground-based surveys conducted on foot by humans, such a system eliminates the potentially large dose that would otherwise be received. With billions of dollars set to be spent on remediation over the coming years; it is crucial to determine the eventual fate and environmental pathways of various radionuclides. It is hoped that this technique will ultimately lead to a better understanding of the hazard, allowing those displaced to return to their homes. As a tool, this instrument is invaluable in locating, as well as identifying the specific isotopic composition of radioactive material, across a range of environments. In addition to locating and quantifying the contamination resulting from a nuclear incident such as Fukushima, the technology has numerous potential applications within the wider nuclear and defence industries. With the potential to assist in the routine monitoring of sites through to the post operational clean-out or in the aftermath of the deliberate dispersion of radioactive material and its associated trafficking.
Keywords: 'UAV'; 'Radiation'; 'Contamination'; 'DSDS16 poster'; 'DSDS16'; 'Aerospace Engineering not elsewhere classified'